STUDI DESKRIPTIF KEMAMPUAN PEDAGOGIK GURU DALAM PEMBELAJARAN SENI BUDAYA DI SMA NEGERI 12 KERINCI JAMBI - Acil Kencana Putra Rm; Yos Sudarman; Harisnal Hadi (FBS Universitas Negeri Padang, 2018)
Abstract This study aims to describe the pedagogic ability of teachers in cultural arts learning in SMA Negeri 12 Kerinci Jambi Province with the target of research were two culture arts teachers who teach Cultural Arts in the school. The method used in this research was qualitative research with descriptive analysis approach. While the object of research was the ability of teachers to implement KBM (Teaching and Learning Activities) in class X and XI SMA Negeri 12 Kerinci. The research instruments used were observation records, interview notes, documentation studies, and questionnaires to support data collection activities with observation techniques, interviews, documentation, and asking for students' responses. The results of the study describe the pedagogical ability of teachers in implementing the KBM, where the ability arises from the knowledge, experience, and talent in teaching which more determine the ability to teach the teachers than mere teachers who only seen from the suitability of educational background. Students of SMA Negeri 12 Kerinci have proved that Ms Mega Silvia has better pedagogic competence than Mr Herman Saidi, although Ms Mega Silvia is not an art diploma background but has a willingness and talent in implementing learning in class.